Analisis Kelayakan Bisnis Untuk Pengembangan Pemasaran Kacang Sangrai Ewooww Yang Luas - Darsiti Darsiti; Ikbal Saepul Ramdan; Naila Syafitri; Widi Aulia Lestari; Wilda Jamila Suryaman; Surya Kurnia Alamsyah (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Roasted Peanuts Ewooww is a Micro, Small and Medium Enterprise that processes peanuts by roasting them. In running his roasted peanut business, ewooww has limitations in shipping because he only has one car, then the next problem is that this business still doesn't rely enough on electronic media. So the aim of this business feasibility study is to provide suggestions that can help Ewooww Roasted Beans in developing its marketing. To determine the feasibility of the project that will be carried out in accordance with the suggestions given, this research uses mixed research, namely by analyzing all aspects in the field, especially the marketing aspect, then reviewing the financial aspects with feasibility analysis in the form of Payback Period, Profitability Index, Net Present Value, Internal rate of Return, and Break Event Points. The results of all feasibility analyzes that have been carried out show positive values so that the suggestions given are worth implementing because they will have a big impact in the following years.